Survey Penggunaan Model Pembelajaran Kooperatif Dalam Muatan IPS Oleh Guru Pada Kelas Tinggi Gugus 4 Cakranegara Tahun Pelajaran 2021/2022 - Levia Aliska Azlianda Huzaini; Nurhasanah; Heri Hadi Saputra (Journal of Classroom Action Research, 2022)
This study aims to determine how the use of cooperative learning models in social studies content by teachers in high grades at SD Gugus 4 Cakranegara in the academic year 2021/2022. This research uses quantitative research with the research design in the form of a survey. This research was conducted at SD Cluster 4 Cakranegara which is divided into six schools namely, SDN 16 Cakranegara, SDN 1 Cakranegara, SDN 34 Cakranegara, SDN 20 Cakranegara, SDN 25 Cakranegara and SDN 9 Cakranegara. The total population in this study were 32 people, and the sample used was 32 people, namely using the entire population. The subjects of this study were teachers of grades 4-6 spread across SD Cluster 4 Cakranegara. In collecting data, researchers used questionnaires and documentation. The data analysis technique used is quantitative descriptive analysis. The results of this study are the implementation of indicators of the use of cooperative learning models in social studies content with a percentage of 83.26%, implementation of indicators of frequency of using cooperative learning models with a percentage of 82.29%, implementation of indicators of cooperative models that are often used with a percentage of 31.56%. So that it can be said that the use of cooperative learning models in social studies content by teachers in high grades at SD Cluster 4 Cakranegara is going well